Biocontrol and growth-promoting potential of endophytic Bacillus subtilis NPA6 against shallot pathogens under sub-optimal land conditions - NUR PRIHATININGSIH; PUJI LESTARI; ZIYADAH MA’RIFATUL ILHAMI; HERU ADI DJATMIKO; IRWANDHI IRWANDHI (Smujo International, 2025)
Abstract. Prihatiningsih N, Lestari P, Ilhami ZM, Djatmiko HA, Irwandhi. 2025. Biocontrol and growth-promoting potential of endophytic Bacillus subtilis NPA6 against shallot pathogens under sub-optimal land conditions. Asian J Agric 9: 607-614. Endophytic Bacillus subtilis NPA6, isolated from rice roots on suboptimal land, has potential as an eco-friendly biocontrol agent for shallot diseases. This study developed liquid biopesticide formulations using coconut water and rice washing water as local carriers, characterized their chemical composition, and tested their effects on shallot disease resistance and growth. A randomized block design with four treatments (control, coconut water formula with NPA6, rice washing water formula with NPA6, and Propineb fungicide) and six replications was used. The coconut water formula contained higher N (0.68%) and Zn (0.36 mg L-1), while the rice washing water formula had higher P (0.74%), K (0.52%), and Cu (0.10 mg L-1). Both formulations reduced disease intensity by 34-36%, comparable to chemical fungicides, although growth and yield parameters were not significantly improved. Correlation analysis revealed a negative relationship between disease intensity and plant height, indicating that disease suppression indirectly contributes to growth maintenance. The novelty of this study lies in utilizing locally available carriers to enhance the performance of B. subtilis NPA6, demonstrating its potential for sustainable shallot cultivation on suboptimal land. Further research should optimize carrier combinations to strengthen both biocontrol and growth-promoting functions.